Economic, environmental and social sustainability in coastal rural tourism development : a case study on The Nauteyri Project in the Westfjords of Iceland - Elliott, Alexander, 1983- (2012)
This thesis concerns the development of a non-profit organisation called The Nauteyri Project, intended to bring sustainable tourism, a nature reserve, environmental and social research options and environmental awareness education to the area of Nauteyri in the Westfjords of Iceland. The Nauteyri Project succeeded in attracting enthusiastic support, but struggled in securing funding. This thesis asks why that was the case, with a view to helping and encouraging similar projects in the future. The question is too multi-faceted to answer directly, so the thesis asks questions pertinent to the whole Westfjords tourism sector. The research questions are related to Sustainable Development in Westfjords tourism, the extent to which tourism should be developed as one of the region‘s core economic pillars, and how the tourism industry in the region should be organised and funded. Semi-structured interviews were conducted with relevant experts in the field. Ten recommendations for future tourism development are presented. Findings include that sustainable tourism development should be encouraged in the region; but that its potential is limited unless more off-season visitors can be attracted. Despite the lack of funding upon first attempt, the thesis concludes that an idea like The Nauteyri Project could have a place in the region‘s future. Lokaverkefni þetta fjallar um þróun sjálfseignarstofnunarinnar The Nauteyri Project, sem ætlað var að setja á fót sjálfbæra ferðaþjónustu, náttúruverndarsvæði, umhverfis- og félagsfræðileg rannsóknartækifæri, og fræðslu í umhverfisvitund til Nauteyrar á Vestfjörðum. The Nauteyri Project fékk mikinn stuðning, en tókst ekki að afla nægjanlegs fjármagns. Lokaverkefnið spyr því hvers vegna þetta gerðist með þessum hætti, með það að markmiði að hjálpa og hvetja til sambærilegra verkefna í framtíðinni. Spurningin er of margþætt og flókin til að svara beint, þannig að lokaverkefnið spyr spurninga sem eru mikilvægar fyrir alla ferðaþjónustu á Vestfjörðum. Rannsóknarspurningarnar tengjast ...